Late-Onset Sepsis in Very Low Birth Weight Premature Infants: a 10-Year Review of a Brazilian Tertiary University Hospital-the Challenge Remains - Gerios, Ludmila [UNESP]; Rodrigues, Victor H. B. [UNESP]; Corrente, Jose E.; Lyra, Joao C. [UNESP]; Rugolo, Ligia M. S. S. [UNESP]; Bentlin, Maria R. [UNESP] (Thieme Medical Publ Inc, 2023)
Objectives This study aimed to assess the incidence of late-onset sepsis (LOS), associated risk factors, and short-term prognosis in very low birth weight (VLBW) infants in a 10-year period.Study Design A cohort study was conducted with 752 VLBW preterm infants-23 to 33 gestational weeks and 400 to 1,500 g birth weight-admitted to a neonatal intensive care unit from 2008 to 2017 and who survived over 72 hours. LOS was defined as clinical and laboratory signs of infection, whether or not confirmed by blood culture. VLBW infants were divided into groups and compared: no LOS versus proven LOS versus clinical LOS. Study variables included maternal, birth, and neonatal data, morbidities, procedures, etiological agents, and outcome-death, bronchopulmonary dysplasia (BPD), severe intraventricular hemorrhage, and retinopathy of prematurity (ROP). Analysis of variance with multiple Tukey's or Wald's comparison with gamma distribution, and stepwise multiple logistic regression model, adjusted for year, and gestational age, were used for statistical analysis.Results LOS incidence was 39% (proven LOS: 29%; clinical LOS: 10%). Septic VLBW infants showed higher mortality (proven LOS: 23.2%; clinical LOS: 41.9%) compared with no LOS (8.9%). Coagulase-negative staphylococci (56%), Gram-negative (26%), and fungi (8%) were the most frequent etiological agents. In comparing the groups, septic VLBW infants had lower gestational age and birth weight, presented more morbidities, and underwent more invasive procedures. The risk factors for proven and clinical LOS were days of mechanical ventilation and parenteral nutrition. LOS was associated with increased risk of death, BPD, and ROP.Conclusion LOS showed high incidence and mortality, often caused by Gram-positive bacteria. Care interventions were the main risk factors associated. LOS had a major negative impact on short-term prognosis in VLBW infants. LOS reduction strategies are necessary and urgent.
Keywords: neonatal sepsis; premature infant; very low birth weight; prognosis; risk factor